(untitled) (Medico Legal Update, 2020)
Introduction: Although many techniques are available for management of oroantral communication, they utilize single layer tissue for closure of defect which is composite in nature. There is limited evidence in literature regarding efficacy of double layered closure using combination of flaps. This study was designed to assess utility of double layer closure of oroantral communication using buccal fat pad and buccal mucosa advancement flap. Material and Method: Patients with oroantral communication were randomly allocated to two groups; group A were treated with two layered closure (buccal fat pad and buccal mucosa) and group B were treated with single layer closure (buccal fat pad). Same protocol of perioperative management was used for both groups. The postoperative parameters evaluated included success of surgery (complete closure without any nasal regurgitation), duration of surgery, pain, swelling and mouth opening. Results: Total of 27 patients were divided into group A (n=13) and group B (n=14). The mean size of the defect was 28.23 mm in study group and 24.57 mm in the control group. The surgical procedure took more time (42.23 minutes) in group A, as compared to group B (26.21 minutes). Post-operative evaluation of pain and mouth opening showed no statistically significant between the two groups at 7th and 30th postoperative days respectively. However, swelling was relatively more when combination of buccal fat pad and buccal advancement flap was used. Conclusion: Double layered closure is efficient in management of OAC. No dehiscence of flap was seen in study group. Comparatively 3 dehiscence was observed in control group, especially with large size defect. The postoperative sequel in both groups was similar.